Answer :


Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation a = 2; b = a; c = - a2


= - 2.a2 = - 2 a2


And either of their sum or difference = b


= a


Thus the two terms are 2a and - a


Difference = 2a - a = a


Product = 2a. - a = - 2a2




2x (x + a)-a (x + a) = 0


(2x-a) (x + a) = 0


(2x-a) = 0 or (x + a) = 0



Hence the roots of equation are


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses